Dendritic Cell Activating Receptor 1 (DCAR1) Associates With FcεRIγ and Is Expressed by Myeloid Cell Subsets in the Rat - Daws, Michael R.; Nakken, Britt; Lobato-Pascual, Ana; Josien, Régis; Dissen, Erik; Fossum, Sigbjørn (Frontiers in Immunology, 2019)
Dendritic cell activating receptor-1 (DCAR1) is a cell-surface receptor encoded by the Antigen Presenting Lectin-like gene Complex (APLEC). We generated a mouse monoclonal antibody against rat DCAR1, and used this to characterize receptor expression and function. Rat DCAR1 was expressed on minor subsets of myeloid cells in lymphoid tissue, but was uniformly expressed at a high level by eosinophils, and at a low level by neutrophils. It was expressed by eosinophils in the peritoneal cavity and the lamina propria of the gut, and by subsets of macrophages or dendritic cells at these sites. Polarization of peritoneal macrophages showed that DCAR1 expression was absent on M1 macrophages, and increased on M2 macrophages. DCAR1 could be expressed as a homodimer and its associated with the activating adaptor protein FcεRIγ. This association allowed efficient phagocytosis of antibody-coated beads. Additionally, cross-linking of DCAR1 on the surface of rat eosinophils lead to production of reactive oxygen species. These data show that DCAR1 is an activating receptor. Its expression on M2 macrophages and eosinophils suggests that it may play a role in the immune response to parasites.